ABU NASR AL-FARABI'S PEDAGOGICAL IDEAS. ABU ALI IBN SINA ON EDUCATION AND UPBRINGING - Pardayeva , Mahfuza; Abdug’afforova , Zarnigor (Journal of Pedagogical and Philological Research, 2026)
This article beautifully highlights Abu Nasr al-Farabi’s life path and his contributions to science. It elucidates the pedagogical thoughts and ideas presented in his works, as well as his perspectives on the process of education and upbringing. Furthermore, it discusses the application of Abu Nasr al-Farabi’s works in today's modern education.